"KISSING-ULCER" - ONSET WITH COMPLICATIONS IN SMALL AGE - Lorena Elena Melit; Cristina Oana Marginean; Raluca Damian; Andreea Dinca; Maria Oana Marginean (Amaltea Medical Publishing House, 2016)
Ulcer disease is a pathology with low incidence in pediatric population, with an unspecific symptomatology or even absent, thus leading to the development of complications. We present the case of 2 years and 10 monthold male patient, admitted in the regional hospital with the diagnosis of febrile acute gastroenteritis, who in evolution (after 5 days) associated digestive hemorrhage, thus being transferred in the Pediatrics Clinic I, Targu-Mures. The superior digestive endoscopy performed after the hemodynamic and metabolic re-equilibration, pointed out 2 ulcers in the duodenal mucosa, one with active bleeding. The treatment with proton pump inhibitors and the adequate diet initiated determined the patient's favorable evolution. The particularity of the case consists in the appearance of 2 duodenal ulcers of the duodenal mucosa in a small child, without significant personal history, with adequate life conditions, without associated risk factors and without infection with Helicobacter pylori.